Application of Artificial Intelligence (AI) in Teaching and Learning of Social Studies: Problems and Prospects - Ali , Umar Magaji; Nwosu, N.P.; Muhammad , Hamisu Kabir; Akasa, Yakubu Azi (Kashere Journal of Education, 2025)
This paper explores the applications of Artificial Intelligence (AI) in the teaching and learning of social studies, highlighting its potential to transform traditional pedagogies, foster faster critical thinking, and promote historical empathy. It also examines the challenges hindering the seamless adoption of AI in social studies education. By examining current research and literature, the study identifies various ways in which AI can benefit social studies instruction, including personalised learning, adaptive assessment, enriched content delivery, immersive simulations, language support, data-driven insights, teacher support, and global collaboration, as well as motivating both teachers and learners for knowledge acquisition. The paper also discusses the challenges and opportunities associated with implementing AI in Social Studies education and highlights the importance of ethical considerations and equitable access. Some of the challenges are addressing unequal access to AI technology and ensuring AI-generated content is unbiased. The opportunities include customised learning experiences for students and enhanced engagement through interactive AI-tools. Through a comprehensive analysis of scholarly works and case studies, this paper offers ideas about the transformative role of AI in shaping the future of Social Studies education.